A Catalog of X-Ray Point Sources in the Abell 133 Region - Shin, J.; Plotkin, Richard; Woo, J.; Gallo, E.; Mulchaey, J. (Institute of Physics Publishing, 2018)
© 2018. The American Astronomical Society. All rights reserved.. As an evolutionary phase of galaxies, active galactic nuclei (AGNs) over a large range of redshifts have been utilized for understanding cosmic evolution. In particular, the population and evolution of AGNs have been investigated through the study of the cosmic X-ray background in various fields. As one of the deep fields observed by Chandra, with a total of 2.8 Ms exposures, Abell 133 is a special region for investigating AGNs, providing a testbed for probing the environmental effects on AGN triggers, since cluster environments can be different from field environments. The achieved flux limits of data at the 50% completeness levels of 6.95 ×10-16, 1.43 ×10-16, and 1.57 ×10-15 erg s-1 cm-2 are 0.5-8, 0.5-2, and 2-8 keV. Using the wavdetect and no-source binomial probability (i.e., p < 0.007), we analyze the combined Chandra image, detecting 1617 (in 0.5-8 keV), 1324 (in 0.5-2 keV), and 1028 (in 2-8 keV) X-ray point sources in the Abell 133 region. Here, we present the X-ray point source catalog with the source fluxes, which can be combined with multiwavelength data for future works. We find that the number count distribution of the X-ray point sources is well reproduced with a broken power-law model, while the best-fit model parameters are sensitive to the fitting range of the number count distribution. Finally, we find an excess of number density (a decrease of AGN fraction) at the central region of the cluster, which reflects the effect of dense environments on AGN triggers, a finding similar to those of other studies of galaxy clusters.